Sexual self-schema and sexual aggression of male readers of Lad Magazines - Aspero, Maris Pylene P.; Faramiran, Zyreen Lou B. (2013.)
This study was conducted to find out the impact of reading lad magazines on the sexual self-schema, and sexual aggression of men. One hundred men of fifty readers and fifty non-readers of lad magazines, from male domintaed insttitution, 18-30 years old served as participants of this study. A survey was conducted and four (4) instruments were used to measure the readership, sexual self-schema, and sexual aggression of man. The design of this study was correlational. To show relationship between variables, data were analyzzed using the pearson -r correlational statistics. The results of this research show that readership of lad magazines is associated with high sexual self-schema in the study sample and the likelihood of being sexually aggressive in comparison to non-readers. Men learned information regarding sex through lad magazines. These magazines also present women in a sexually arousing manner through their pictures and articles. Men's lifestyle was also affected by their readership of lad magazines.
Research Project (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2013
Keywords: Lad Magazines -- Readers